2021
DOI: 10.1093/texcom/tgab001
|View full text |Cite
|
Sign up to set email alerts
|

Mind-wandering Is Accompanied by Both Local Sleep and Enhanced Processes of Spatial Attention Allocation

Abstract: Mind wandering (MW) is a subjective, cognitive phenomenon, in which thoughts move away from the task towards an internal train of thoughts, possibly during phases of neuronal sleep-like activity (local sleep, LS). MW decreases cortical processing of external stimuli and is assumed to decouple attention from the external world. Here, we directly tested how indicators of LS, cortical processing and attentional selection change in a pop-out visual search task during phases of MW. Participants brain activity was r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Moreover, the frequency of mind-wandering tends to increase after sleep deprivation [25], indicating that accumulated sleep pressure may facilitate the mind to wander. Accordingly, mind-wandering during attention-demanding cognitive tasks is coupled with neurophysiological indicators of local sleep [11,26], supporting the assumption that attentional lapses, sensory disengagement, and spontaneous thoughts are underlined by transient sleep-like neuronal activity [27,28]. The link between sleep pressure and daytime mind-wandering is also corroborated by cross-sectional, questionnaire-based studies that report an association between poor sleep quality and increased mind-wandering [29].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, the frequency of mind-wandering tends to increase after sleep deprivation [25], indicating that accumulated sleep pressure may facilitate the mind to wander. Accordingly, mind-wandering during attention-demanding cognitive tasks is coupled with neurophysiological indicators of local sleep [11,26], supporting the assumption that attentional lapses, sensory disengagement, and spontaneous thoughts are underlined by transient sleep-like neuronal activity [27,28]. The link between sleep pressure and daytime mind-wandering is also corroborated by cross-sectional, questionnaire-based studies that report an association between poor sleep quality and increased mind-wandering [29].…”
Section: Introductionmentioning
confidence: 53%
“…The sleep EEG and self-report data of 67 participants (47 females, mean age: 24.7, Std. Dev: 3.3, range: [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were considered in the final analyses, yielding in total of 464 nights of EEG recordings (missing data: 7%), 485 entries for morning (missing data: 3%), 468 entries for daytime self-reports (missing data: 6%), and 259 entries for dream features (i.e. a relatively larger rate of missing data was expected for dream-related variables since dream recall does not occur every morning).…”
Section: Participants and Final Datasetmentioning
confidence: 99%
“…More importantly, these results provide preliminary evidence supporting the integration of the Control Failure × Concern hypothesis and the Local Sleep framework (Andrillon et al, 2019; Jubera‐Garcia et al, 2021). Poor sleep could increase the level of sleep pressure, which then could induce local sleep in task‐related brain regions, thereby leading to high sensitivity to negative emotion (Gruber & Cassoff, 2014) and poor performance in executive control tasks (Andrillon et al, 2021; Wienke et al, 2021). Besides, local sleep can also influence the contents of subjective experiences such as mind wandering focused on self‐related concerns and emotions (Andrillon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to the Local Sleep framework, local sleep (the sleep-like activity such as slow wave activity and theta waves in the awake brain) intrusions related to sleep loss and poor sleep could predict the occurrences of mind wandering (Andrillon et al, 2019;Jubera-Garcia et al, 2021). The electrophysiological studies have also indicated that mind wandering was accompanied by an increase in slow wave activity, similar to the local sleep (Andrillon et al, 2021;Wienke et al, 2021). The local sleep framework was theoretically used to explain the potential mechanism for ADHD based on the evidence showing the high frequency of mind wandering and sleep disturbance in individuals with ADHD (Andrillon et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…transiently decoupled from the external inputs) that enhances the processing and consolidation of previously encoded material, resembling the mechanisms of sleep-dependent memory consolidation (Jubera-Garcia et al, 2021;Wamsley, 2022;. Accordingly, mind wandering has been linked to decreased evoked potentials, indicating diminished sensory processing (Kam et al, 2022), as well as increased, slow-frequency activity reminiscent of the slow and delta waves observed during non-rapid eye movement (NREM) sleep (Andrillon et al, 2021;Wienke et al, 2021). In addition, sleep-like cortical activity during mind wandering was expressed in a region-specific, topographically localized manner (Andrillon et al, 2021;Wienke et al, 2021), pointing to the links between mind wandering and local sleep (Andrillon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%